Prosedur Pengoperasionalan Pengadaan Barang dan Jasa pada PT Surabaya Industrial Estate Rungkut - Putri, R.A Tania Eriezna; Andarini, Sonja (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Procurement of goods and services is one of the crucial activities in a company. Procedures for the operationalization of procurement of goods and services at PT Surabaya Industrial Estate Rungkut (SIER) are designed to ensure that procurements are carried out in a transparent, efficient manner and in accordance with applicable regulations. The purpose of this research is to exhibit the operational procurement of goods and services on PT SIER. This research method uses qualitative descriptive, so will display the results through observations carried out by the author during the internship. The results of the research show that the operational procurement of goods and services of this PT SIER has three stages: planning, acquisition, and supervision. In its implementation, the procurement division at PT SIER is divided into several units to facilitate coordination with vendors at the time of provision of goods.